1994
DOI: 10.1002/j.1460-2075.1994.tb06299.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cell division revealed by transcriptional regulation of genes during the cell cycle in plants.

Abstract: Transcripts from five cell cycle related genes accumulate in isolated cells dispersed throughout the actively dividing regions of plant meristems. We propose that this pattern reflects gene expression during particular phases of the cell division cycle. The high proportion of isolated cells suggests that synchrony between daughter cells is rapidly lost following mitosis. This is the first time that such a cell specific expression pattern has been described in a higher organism. Counterstaining with a DNA speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
150
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 37 publications
15
150
0
2
Order By: Relevance
“…The in situ experiments showed that the two bZIP genes had different but overlapping patterns of expression in Antirrhinum flowers so, potentially, bZIP911 could function in some places as a homodimer (for example in the endothecium and most of the cells of the carpel) and in others bZIP910 and bZIP911 could potentially interact © Blackwell Science Ltd, The Plant Journal, (1998), 13, 489-505 as heterodimers (for example in the tapetum and vascular tissues of the ovaries). The expression pattern of bZIP911 was similar to the reported pattern of a gene encoding histone H4 in Antirrhinum (Forbert et al, 1994), in particular in the absence of expression in the older bract and sepal primordia and the relatively strong expression in the anthers. This gene encoding histone H4 is relatively highly expressed in the vascular tissue of floral apices, as is bZIP910.…”
Section: Both Bzips Are Expressed Predominantly In Antirrhinum Flowersupporting
confidence: 75%
See 3 more Smart Citations
“…The in situ experiments showed that the two bZIP genes had different but overlapping patterns of expression in Antirrhinum flowers so, potentially, bZIP911 could function in some places as a homodimer (for example in the endothecium and most of the cells of the carpel) and in others bZIP910 and bZIP911 could potentially interact © Blackwell Science Ltd, The Plant Journal, (1998), 13, 489-505 as heterodimers (for example in the tapetum and vascular tissues of the ovaries). The expression pattern of bZIP911 was similar to the reported pattern of a gene encoding histone H4 in Antirrhinum (Forbert et al, 1994), in particular in the absence of expression in the older bract and sepal primordia and the relatively strong expression in the anthers. This gene encoding histone H4 is relatively highly expressed in the vascular tissue of floral apices, as is bZIP910.…”
Section: Both Bzips Are Expressed Predominantly In Antirrhinum Flowersupporting
confidence: 75%
“…Transcriptional activation probably requires interaction with other factors, one possibility being the proteins binding to the neighbouring octomer motif conserved in many histone promoters, another being heterodimerization with other members of the bZIP protein family and yet another being binding to co-activators to increase bZIP activation specificity (Claret et al, 1996). The pattern of bZIP910 and bZIP911 gene expression shows a reasonably good correlation to expression of the gene encoding histone H4 in Antirrhinum inflorescences (Forbert et al, 1994) although post-transcriptional regulation may further modify the amount of each transcription factor active in any one cell.…”
Section: Which Genes Are These Proteins Regulating?mentioning
confidence: 98%
See 2 more Smart Citations
“…HIS4 is expressed only in the S phase of the cell cycle, and only a proportion of the cells give a strong signal in proliferating tissue. CYCD3B, a key regulator of the cell cycle in plants, is not restricted to one phase of the cell cycle and is expressed throughout proliferating tissue (Fobert et al, 1994;Riou-Khamlichi et al, 1999;Gaudin et al, 2000).…”
Section: Growth and Cell Differentiation In Petals Andmentioning
confidence: 99%